Mechanisms of Financial Support As A Factor Determining The Development Of The Organic Farming Sector In The Countries Of European Union - Joanna Rorat; Anna Szelag-Sikora; Marcin Niemiec; Jakub Sikora; Michal Cupial (Institute of Economic Research (IER), 2017)
Agricultural sector of polish national economy is an example of entrepreneurship - especially individual one, dealing with underdevelopment of technological, intellectual and institutional infrastructure what is a serious threat to the usage of potential of the financial resources available due to polish membership in the European Union. The possibility of gaining financial support and entering the European market caused dynamic increase in the number of entities engaged in agricultural activities with ecological characteristics - in Poland and whole EU- and mainly this sector of production is treated with priority in currently realized Common Agricultural Policy in European Union countries. At the same time it should be remarked that managing agricultural companies is aimed at achieving their specific goals of a financial nature - as in other sectors of the national economy. The main aim of this thesis is to show the impact of financial support coming from European Union budget on the pace of development of the organic sector in Poland compared to other European Union countries. To fulfill the aim of the thesis the available financial mechanisms (the level of support, the main criteria for accesses) were characterized as well as legal aspects regulating them on the national level and in selected EU countries. General issues included provide also the characteristics of the problem of European market of ecological products. The study contains an assessment of the current use of the financial resources of the EU (after accession to the EU, i.e. 2004) addressed to organic farming. The thesis has been prepared based on the analysis of subject literature, applicable laws, as well as the documents / reports prepared by the major stakeholders in the country and EU responsible for gaining and gathering information on country level as well as chosen EU countries. In the thesis a comparative analysis has been carried out as well as tabular - numerical analysis with regard to the volatility during the analyzed events. The observed absorption of EU financial resources in the agricultural sector in all European countries - especially in recent years in Poland- shows how big are the needs for financial support of agricultural production for sustaining for example the stability of market prices of food products. In the era of increasing consumer awareness on the rational nutrition we observe revival of market of organic products. However the increase in market absorptive capacity is the only factor determining the development of ecological agriculture? Or are there any other financial support mechanisms? High subsidy rates (an average of approx. 950 PLN/ha and growing every year, with an average area of ecological farms above 20 ha) caused a significant increase in the number of ecological farms (within 10 years of joining the EU over 1400%). It is reasonable to assume that as long as there will be economic incentives, business farmers will be interested in the transition to an ecological way of farming, an example of which are other EU countries.
Keywords: Q12; Q14; 330; EU funds; agricultural development; eco products market